BANDITRY AND GENDER-BASED VOLIENCE IN NORTH-WEST NIGERIA - Simon Nankap KUMS; Cornelius Ishaya KWEDE (International Studies Journal)
The menace of banditry over the years had had a devastating effects on both developed and developing countries of the world alike. This emerging security challenge has threatened the very fabric of the fragile peace the Nigerian State was enjoying; especially, in the Northwest states of Zamfara, Kaduna, Katsina, etc. However, the paper examines the impact of banditry activities on women and children who are mostly victims. This study uses a qualitative methodology that relies on secondary data sources. Books, periodicals, newspapers, online information, and reports were frequently used. The paper posits that the presence of high level of unemployment with the attendant poverty, weak security system, grossly ungoverned spaces, porosity of Nigeria’s borders, and arms proliferations, among many, are the driving factors quickening banditry in the Northwest region of Nigeria. It further contends that the banditry activities pervading the Northwest Nigeria has undermined human security; peace and development of the region and that the efforts made by stakeholders to combat the scourge have not yielded the desired result. The paper hence recommends, among others, that  the Nigerian government should come up with working poverty alleviation programme(s) and should be directed towards addressing the high incidence of poverty among women and children who are a vulnerable segment of the population mostly attacked and trapped by banditry activities vis-à-vis empowerment programmes or employment opportunities, targeting youths who are primarily involved in abductions and kidnappings out of economic frustration, such as unemployment; and also establish a special force and intelligence unit that will be trained and equipped to fight against human trafficking, banditry, kidnapping and terrorism, as this will help in curtailing if not eliminating criminal activities in our society.